PENGARUH PROGRAM PINJAMAN KREDIT CINTA RAKYAT (BANK BJB) TERHADAP PERKEMBANGAN MITRA BINAAN (UMKM) DI DINAS KOPERASI DAN USAHA KECIL PROVINSI JAWA BARAT (TAHUN 2013-2015) - YUSUF, RAMAYANI; PUTRI LARASATI, NICKY (Jurnal E-Bis (Ekonomi-Bisnis), 2017)
The purpose of the research is to analyze the effect of â€œPinjaman Kredit Cinta Rakyatâ€(BJB Bank) for partners development (UMKM) in Cooperative service and micro business west java province (years 2013-2015). The method that writer used is quantitative analysis method, that is method which try to give systematic image, factualand accurate. And the data collecting technic are survey and questioner. Result of the research from 2013 show that 1) Calculation of correlation coefficient was 0,470 which shows that strong enough of correlation or relation existence, 2) Analysis of regresi linear sederhana shows coefficient value (b) positive which means if Kredit Cinta Rakyat (KCR) is increasing either, 3) Calculation of determination coefficient is 0,221 or 22,1% that shows Kredit Cinta Rakyat (KCR) is giving contribution for about 22,1% for micro, small and medium business (UMKM) and 77,9% effected by other factors. From the previous a research, there was trouble appeared such as: 1) Difficulty of many debitors to pay the debt, 2)The money they got form KCR is not used for their priorities, 3) Lack of awareness for what should be responsible, 4) The procedure of KCR was not effective, 5) Lack of knowledge from subject of micro, small and medium business (UMKM) about limitation and time period. . The advice given by the author to overcome the existing problems are; 1) We recommend that the Bank prior to credit loan first conduct a survey to the field to know the development of partners built (UMKM), 2) Preferably before making a loan loan, the perpetrators of Micro, Small and Medium Enterprises (UMKM) are ready to bear all the consequences that will faced after the loan is fulfilled, 3) It is better to simplify the Bank to give credit, the perpetrators of Micro, Small and Medium Enterprises (UMKM) first trained for the funds are used properly.